LOCAL CEREAL FLOURS REPARTITION ON MARKETS AND SELLERS APPROACH ON PRODUCTION AND CONDITIONING IN THE DISTRICTS OF ABIDJAN COTE D’IVOIRE - Yevi D. Nguessan; Micael E. Bedikou; Rose-Monde Megnanou; Sebastien L. Niamke (European Scientific Journal, ESJ, 2014)
In Côte d’Ivoire, cereals are traditionally grown in northern areas. After production, they are generally transformed into flours and consumed mainly as staple foods in form of thin and thick porridges or alcoholic or non-alcoholic beverages. However, constraints to traditional processing of local cereals have led to a shift towards adoption of quality, easy to cook imported cereal products. Mechanization of the hulling and milling steps for flours production has become a way to valorize local cereals. This survey help assert that millet and maize flours were the main local cereal flours produced and sold on the markets. No significant difference was found between the numbers of women processors of millet, white and yellow maize flours identified (P<0.05). Preference between the local cereal flours showed that on a 1 to 3 scale comparison (P<0.05), millet flour ranked as being the most prized followed by white maize and then yellow maize. The yellow maize owes its popularity to addition of alkaline ash. In terms of volumes of production and sale, maize flours were the most important (P<0.05). As far as quality was concerned, the wet processing and the ignorance of hygiene practices observed are limiting factors.